Fast quantitative three‐dimensional ultrashort echo time (UTE) Cones magnetic resonance imaging of major tissues in the knee joint using extended sprial sampling. (15th July 2020) - Wan, Lidi; Ma, Yajun; Yang, Jiawei; Jerban, Saeed; Searleman, Adam C.; Carl, Michael; Le, Nicole; Chang, Eric Y.; Tang, Guangyu; Du, Jiang
Abstract : The purpose of this study is to investigate the effect of extending the spiral sampling window on quantitative 3D ultrashort echo time (UTE) Cones imaging of major knee joint tissues including articular cartilage, menisci, tendons and ligaments at 3 T. Nine cadaveric human whole knee specimens were imaged on a 3 T clinical MRI scanner. A series of quantitative 3D UTE Cones imaging biomarkers including T2 *, T1, adiabatic T1ρ, magnetization transfer ratio (MTR) and macromolecular fraction (MMF) were estimated using spiral sampling trajectories with various durations. Errors in UTE MRI biomarkers as a function of sampling time were evaluated using a nonstretched spiral trajectory as a reference standard. No significant differences were observed by increasing the spiral sampling window from 1116 to 2232 μs in the calculated T2 *, T1, adiabatic T1ρ, MTR and MMF, as all P ‐values were over .05 as assessed by ANOVA with two‐sided Dunnett's test. Although extending the sampling window results in signal loss for short T2 components, there was limited effect on the calculated quantitative biomarkers, with error percentages typically smaller than 5% in all the evaluated tissues. The total scan time can be reduced by up to 54% with quantification errors of less than 5% in any evaluated major tissue in the knee joint, suggesting that 3D UTE Cones MRI techniques can be greatly accelerated by using a longer spiral sampling window without causing additional quantitative bias. Abstract : Extending the sampling window would result in signal loss, particularly for short T2 components. However, extending the sampling window has a limited effect on quantitative 3D UTE Cones imaging biomarkers including T2 *, T1, adiabatic T1ρ, magnetization transfer ratio (MTR) and macromolecular fraction (MMF), with error percentages typically smaller than 5% in all evaluated tissues when the sampling window is 2232 μs. The total scan time can be reduced by 54% in any evaluated major tissue in the knee joint.